2021
DOI: 10.1016/j.ultsonch.2021.105709
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted transesterification of soybean oil using low power and high frequency and no external heating source

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…These conventional techniques have a few limitations for high-FFA oil, such as a slow reaction rate, a long reaction time and high energy consumption, resulting in a low FFA conversion yield. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Since methanol and oil are immiscible, making effective contact during the reaction is difficult and leads to slower conversion rates and longer reaction periods. Accelerating processes with cavitation can assist in getting around reactant immiscibility.…”
Section: Statement Of Noveltymentioning
confidence: 99%
See 2 more Smart Citations
“…These conventional techniques have a few limitations for high-FFA oil, such as a slow reaction rate, a long reaction time and high energy consumption, resulting in a low FFA conversion yield. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Since methanol and oil are immiscible, making effective contact during the reaction is difficult and leads to slower conversion rates and longer reaction periods. Accelerating processes with cavitation can assist in getting around reactant immiscibility.…”
Section: Statement Of Noveltymentioning
confidence: 99%
“…There have been reports on process development using ultrasound waves with a single frequency. It has been determined that ultrasound waves can enhance the efficacy of esterification [22][23][24][25][26][27][28] and transesterification [29][30][31][32][33][34][35][36] by significantly reducing the reaction time and the required excess M:O molar ratio, and increasing the conversion rate of FFAs with respect to conventional mechanical stirring. For intensifying these reactions, sonochemical reactors with ultrasonic baths and ultrasonic horn irradiation types have been used.…”
Section: Statement Of Noveltymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this emerging approach can be adapted to provide the more efficient biodiesel production process. Another study by Oliveira and co-workers reported that the removal of external heating source and mechanical agitation is beneficial for ultrasonic assisted transesterification process (Oliveira et al, 2021).…”
Section: Ultrasonic Assisted Biodiesel Synthesismentioning
confidence: 99%
“…Oliveira el al. [16] evaluated the effect of low power and high-frequency ultrasound (1 to 3 MHz) on the transesterification of soybean oil, without the aid of external source and mechanical stirring. According to the authors, this approach can make the system even more environmentally friendly and economical for industrial applications.…”
mentioning
confidence: 99%